2022
DOI: 10.4037/ajcc2022451
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Aging Brain Care Monitor, Caregiver Version: Screening for Post–Intensive Care Syndrome

Abstract: Background Cognitive impairment is common in intensive care unit survivors, pointing to the potential utility of a caregiver-based tool to screen for post–intensive care syndrome. Objective To validate the Healthy Aging Brain Care Monitor, Caregiver Version (HABC-M CG), as a caregiver-based tool to screen for post–intensive care syndrome. Methods A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Measurement properties of the HABC-M-HV-F seem consistent with those obtained from the original versions of the HABC-M in PICS context [ 7 , 8 ]. For these versions, authors observed similar internal consistency, and similar findings regarding convergent validity.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Measurement properties of the HABC-M-HV-F seem consistent with those obtained from the original versions of the HABC-M in PICS context [ 7 , 8 ]. For these versions, authors observed similar internal consistency, and similar findings regarding convergent validity.…”
Section: Discussionsupporting
confidence: 72%
“…Two versions were developed and validated: The Caregiver Report Version (31-item questionnaire) relied on the observations and perceptions of the patient’s informal caregiver [ 5 ], while the Self-Report Version (27-item questionnaire) was utilized to collect information directly from the patient [ 6 ]. Both versions have recently been validated for PICS screening [ 7 , 8 ]. During the implementation of these tools in daily practice, their authors used an agile implementation process [ 9 ] to meet the changing local needs and to deal with the local context.…”
Section: Introductionmentioning
confidence: 99%
“…The m-CCRP intervention was led by a nurse care coordinator who conducted patient visits at home and health care facilities, collaborated weekly with the m-CCRP interdisciplinary team (critical care physicians, geriatrician, ICU nurse, and neuropsychologist), worked with patients’ physicians, coordinated health care appointments, implemented care plans, and monitored recovery (eMethods in Supplement 2 ). Within 1 week of randomization, the care coordinator assessed patients at their place of residence using the Healthy Aging Brain Care Monitor (HABC-M; scores ranged from 0 to 81, with higher scores indicating higher cognitive, functional, and behavioral symptom burden), 21 , 22 , 23 Mini Mental State Examination (MMSE; scores ranged from 0 to 30 with higher scores indicating improved cognition), 24 Timed Up and Go test (scores ≤10 seconds were considered normal, and scores ≥14 seconds suggested high risk of falls), 25 activities of daily living (Katz scale; scores range from 0 to 6, with higher scores indicating higher independence), 26 instrumental activities of daily living (Lawton Scale; scores ranged from 0 to 8, with higher scores indicating higher independence), 27 Hospital Anxiety and Depression Scale (HADS; scores ranged from 0 to 21, with higher scores indicating higher anxiety and depression), 28 Pain screening tool (Pain, Enjoyment of Life and General Activity [PEG]; scores ranged from 0 to 10, with higher scores indicating higher pain), 29 and the Patient-Reported Outcomes Measurement Information System (PROMIS) Sleep Disturbance short form 4a (scores ranged from 4 to 20, with higher scores indicating poor sleep). 30 The care coordinator, with input from the m-CCRP team, prepared and delivered the care plan to the patient within 2 weeks of the initial assessment.…”
Section: Methodsmentioning
confidence: 99%
“…The mean (SD) age of the enrolled study participants was 56.1 (14.4) years, 250 (53.6%) were female, 216 (46.4%) were male, 172 (36.9%) were African American, and 280 (60.1%) were White, 7 were categorized as other (individual numbers are not provided to prevent identification), and the race and ethnicity of 13 patients was unknown. Patients had a median (IQR) APACHE-II score of 25 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) and a median (IQR) Charlson Comorbidity index of 2 (1-3) (Table 1).…”
Section: Participant Characteristicsmentioning
confidence: 99%